2008
DOI: 10.1186/1472-6947-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Towards pervasive computing in health care – A literature review

Abstract: Background: The evolving concepts of pervasive computing, ubiquitous computing and ambient intelligence are increasingly influencing health care and medicine. Summarizing published research, this literature review provides an overview of recent developments and implementations of pervasive computing systems in health care. It also highlights some of the experiences reported in deployment processes. Methods:There is no clear definition of pervasive computing in the current literature. Thus specific inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(135 citation statements)
references
References 65 publications
2
128
0
5
Order By: Relevance
“…This finding echoes an earlier review of mHealth initiatives in developing countries (Chib, 2013). One of the barriers to providing such evidence is revealed in the common criticism that the majority of previous published mHealth initiatives are prototypes, pilots or tests (Orwat, Graefe, & Faulwasser, 2008) which do not readily upscale to national-level systems (van Heerden, Tomlinson, & Swartz, 2012). A number of critics have attributed this limited scalability to the predominant techno-centric philosophy which underpinned early mHealth projects in the region (e.g.…”
mentioning
confidence: 58%
“…This finding echoes an earlier review of mHealth initiatives in developing countries (Chib, 2013). One of the barriers to providing such evidence is revealed in the common criticism that the majority of previous published mHealth initiatives are prototypes, pilots or tests (Orwat, Graefe, & Faulwasser, 2008) which do not readily upscale to national-level systems (van Heerden, Tomlinson, & Swartz, 2012). A number of critics have attributed this limited scalability to the predominant techno-centric philosophy which underpinned early mHealth projects in the region (e.g.…”
mentioning
confidence: 58%
“…Comparison with previous literature Other reviews have looked at the use of context awareness in health care [4,18]. Bricon-Souf (2007) found that there was a large gap between the requirements expressed by users, and the contextaware prototypes developed.…”
Section: Context Elements and Technologies Of Current Interventionsmentioning
confidence: 96%
“…A common issue in context-aware systems research is the challenge of evaluating their real-world implementation [4,18]. Implementation fidelity is "the degree to which programs are implemented as intended by the program developers" [24].…”
Section: Implications For Research and Healthcarementioning
confidence: 99%
“…There is a large variety of sensors used to monitor SHs and the residents. Sensors are used to collect various types of data related to [83]:…”
Section: Sensorsmentioning
confidence: 99%